Gaya Bahasa Satire dalam Talkshow Mata Najwa “Jenaka di Negeri Opera” - Titin Azhari; Hermandra Hermandra; Elvrin Septyanti (Journal on Education, 2023)
This study aims to describe the form of satirical language style used by the interviewees in Mata Najwa's talk show "Jokes in the country of opera", to explain the meaning of the satirical language style used by the speakers in Mata Najwa's talk show "Jokes in the country of opera", and to explain the function of the satirical language style used resource person in Najwa's eye talk show "funny in the land of opera". This type of research is qualitative research. This study uses a descriptive analytic method, namely by analyzing and describing descriptively the data obtained in the study, broken down into words not numbers. Methods of data collection in this study using the method of documentation and notes. The data analysis techniques used were data reduction, data presentation, verification, and conclusions. The results of this study are the speeches of the informants in the Mata Najwa talk show "Jokes in the Land of Opera" which contain satirical language styles. The data source for this research is Mata Najwa's YouTube channel with a video titled "Jenaka in the Land of Opera" part 1 to.d. 7. The data found were 44 satire language data in Najwa's eye talk show "jokes in the country of opera" consisting of 17 Horatian satire data, 14 juvenile satire data, and 13 menippean satire data.